Bimolecular recombination in methylammonium lead triiodide perovskite is an inverse absorption process - Christopher L. Davies (Nature Portfolio, 2018)
Radiative bimolecular processes will dominate charge-carrier recombination in hybrid perovskite solar cells operating near the Shockley-Queisser limit. Here, the authors show that such processes are the inverse of absorption and increase as distribution functions sharpen towards lower temperatures.